2001
DOI: 10.1159/000056614
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Discomfort of Ten-Core Biopsy of the Prostate Evaluated by Questionnaire

Abstract: Transition zone biopsies have been found to increase the detection rates of cancer of the prostate in patients with negative digital rectal examination. There are however no data available whether the higher biopsy rate is associated with greater morbidity. The present study was therefore designed to evaluate the complication rate of extended sextant biopsy. In this prospective study, 162 consecutive patients who presented for prostatic evaluation were included. After starting prophylactic antibiotic treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Regarding the complications biopsy procedure the present study showed that rectal bleeding and urinary tract infection were observed 2(6.7%) and 1(3.3%) in group I and group II respectively. The same complication were found in 2% of case in the study in their series 3,19,20,21 . In the current study urinary tract infection was 2(6.7%) in group I and 1(3.3%) in in group II.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Regarding the complications biopsy procedure the present study showed that rectal bleeding and urinary tract infection were observed 2(6.7%) and 1(3.3%) in group I and group II respectively. The same complication were found in 2% of case in the study in their series 3,19,20,21 . In the current study urinary tract infection was 2(6.7%) in group I and 1(3.3%) in in group II.…”
Section: Resultssupporting
confidence: 60%
“…This difference was significant (p<0.05). Including the degree of pain after 30 minutes of biopsy and duration of pain, were not significantly (p>0.05) different between the two groups 19,20 . The results obtained in above authors is strongly support the present study, where the pain degree during biopsy it was found that most patients had mild pain in group I which was 13(50.0%) and in group II no pain was predominant which was 13(43.3%) of the patients.…”
Section: Resultsmentioning
confidence: 77%
“…Modern prostate biopsy with the appropriate antibiotic prophylaxis has an acceptable safety margin, but mild haematuria, haematospermia and rectal bleeding are common. Table 3 summarizes the previous publications on the complication rates after prostate biopsy, classified according to the number of cores taken [3,6,7,10–27].…”
Section: Discussionmentioning
confidence: 99%
“…After this procedure, mild rectal bleeding may occur in 0-25% of patients [2, 3]. Other complications include self limiting hematuria, hematospermia and urinary tract infection, most of which resolve with conservative therapy [4, 5].…”
Section: Introductionmentioning
confidence: 99%